2016
DOI: 10.1016/j.rppede.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with caries: a survey of students from southern Brazil

Abstract: Objective:To describe the factors associated with dental caries among students from Santa Cruz do Sul, Rio Grande do Sul, Brazil.Methods:A cross-sectional study was conducted in a random sample of 623 students of both genders, aged 10-17 years old. Tooth decay was performed using the index of the World Health Organization (1997), DMFT (permanent dentition) that expresses the sum of decayed, missing and filled teeth per person. The maternal educational level was rated using criteria of the Brazilian Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
(11 reference statements)
0
9
1
1
Order By: Relevance
“…In addition, it was determined that the mothers' working affected the DMFT point average of children. Borges et al (2015) in study of 623 students aged 10-17 in Brazil reported a significant difference in the percentage of children whose mothers completed their 4-year educational life [24]. In our study, the difference between the educational background of parents and DMFT point average of children was not significant.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In addition, it was determined that the mothers' working affected the DMFT point average of children. Borges et al (2015) in study of 623 students aged 10-17 in Brazil reported a significant difference in the percentage of children whose mothers completed their 4-year educational life [24]. In our study, the difference between the educational background of parents and DMFT point average of children was not significant.…”
Section: Discussioncontrasting
confidence: 69%
“…55.9% of the children were consuming junk food every day as show in Table 6.The DMFT average of children who consumed junk food every day was very high found as 5.11 ± 3.67 in Table 6.In Gökalp and Doğan's study (2004),which examined to treatment needs of 5-12 and 15 years old children and 35-44 years old and 65-74 years old adult (n = 7833), it found that tooth decay rate of 5 years old was 69.8%, 12 years old was 61.1% , and 15 years of age was 66.4% [22]. Jessri et al (2013) found DMFT mean of 2.51 ± 2.14 in school children aged 9-13 in Tehran (n = 1271) [23] and Borges et al (2016) in Brazil with 623 students in the 10-17 age group reported an average DMFT of 2.5 [24]. Koçanlı et al (2014) found a positive correlation between the frequency of dietary food intake and child caries index values in their study with 300 children aged 7-13 years [25].…”
Section: Discussionmentioning
confidence: 99%
“…Risks for the development of dental caries include environmental factors, nutritional factors, behavioral factors, socioeconomic and socio demographic factors. Other factors include oral salivary flow and composition, presence of cariogenic bacteria, immune components and genetic factors [ 19 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significantly higher number of children had poor oral hygiene status, moderate to severe caries experience as a result of less frequency of brushing, poor oral hygiene knowledge and irregular dental checkup. 11 In this cross sectional study we found the total DMFT is found out to be 79 with 51decayed teeth, 25 missing teeth and 3 filled teeth. The mean DMFT is found out to be…”
Section: Discussionmentioning
confidence: 65%